The kindness of strangers: Trust, recognition, and the co-production of desistance - Ugelvik, Thomas (Theoretical criminology, 2025)
This article explores the significance of new relationships between former offenders who have made changes to their lives and the people they meet as part of their desistance journeys. Many studies of individual desistance processes have focused on the experience of stigma and exclusion, but the related concept of trust rarely appears in the literature. What does it mean for ongoing desistance and identity reconstruction processes when strangers are willing to take a chance and place trust in former offenders? Through a close look at the connections between desistance processes and the experience of mutual interpersonal trust, this article examines the role trust may play in the co-production of desistance.